Awareness of ceramic workers on occupational health hazard and related preventive practice - Nahar, Lutun; Rahman, Shafiur; Smrity, Jarjina Akter; Begum, Farjana; Afroze, Rushan; Khan, Prianka (International Journal of Research in Medical Sciences, 2025)
Background: The ceramic industry is one of the significant manufacturing sectors in Bangladesh, where workers are often exposed to various occupational health hazards. This study aimed to assess the awareness of ceramic workers regarding these hazards and the associated preventive practices in Dhaka’s Mirpur Ceramics Works Ltd., the largest structural clay products manufacturer in Bangladesh. Methods: A cross-sectional survey was conducted from 1st January to 31st December, 2022, involving 267 workers. Data were collected through face-to-face interviews using a semi-structured questionnaire that assessed socio-demographic characteristics, work-related factors, and awareness of occupational hazards, hazard identification, and preventive practices. Results: The study found that most workers were aware of general health hazards 88.4% and hazardous materials 95%. However, awareness regarding safety regulations and hazard management was low, with only 34% and 33.3% aware, respectively. Specific physical hazards, such as noise, heat, and poor ventilation, were recognized by a significant proportion of workers 81-82%, but awareness of chemical hazards was minimal 1.9%. Ergonomic hazards were also poorly understood, with only 43.8% aware of risks related to awkward sitting and manual product handling. The study revealed that 60.7% of workers had low awareness levels, with a statistically significant association between gender and awareness, particularly among male workers. Conclusions: The study highlights a significant gap in the awareness of occupational health hazards among ceramic workers in Bangladesh. The findings emphasize the need for targeted occupational safety training and awareness programs, especially focusing on chemical and ergonomic risks.